2001
DOI: 10.1055/s-2001-12407
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Intramyocellular Lipids (IMCLs) During Exercise as Assessed by Proton Magnetic Resonance Spectroscopy (1H-MRS)

Abstract: Recently, a 1H-MRS method became available to quantify intramyocellular lipids (IMCL) non-invasively. Currently, little is known about the regulation of this lipid pool. During prolonged exercise of moderate intensity, non-plasma-derived fatty acids play an important role as an energy source; lipids located within the skeletal muscle are considered to be a major source for these fatty acids. To see whether IMCL are reduced by exercise, 12 male runners were studied before and after exercising at different workl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
85
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 9 publications
(17 reference statements)
9
85
2
1
Order By: Relevance
“…Boesch et al (2) revealed a decrease of IMCL in one subject performing a mountain bike ride over 3 h at about 70% of VO 2max , for the first time using 1 H-MRS to demonstrate that IMCL are metabolized during this form of exercise. In the following years, numerous reports on reduced IMCL levels during exercise were published and reviewed (17,20,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). It became obvious that both exercise duration and intensity are important factors in determining the reduction of IMCL (39).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
“…Boesch et al (2) revealed a decrease of IMCL in one subject performing a mountain bike ride over 3 h at about 70% of VO 2max , for the first time using 1 H-MRS to demonstrate that IMCL are metabolized during this form of exercise. In the following years, numerous reports on reduced IMCL levels during exercise were published and reviewed (17,20,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). It became obvious that both exercise duration and intensity are important factors in determining the reduction of IMCL (39).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
“…At an intensity of 80% VO 2 max glycogen stores will be emptied in about 90-180 min 31 and at this intensity, 80% of the energy derives from carbohydrate oxidation 32 of the muscle glycogen, whereas the oxidation of intramuscular triglycerides is inhibited. 33 At even higher intensities, muscle glycogen is oxidized anaerobically and the concentration of lactate will rise to values around 5 mmol/l. 34 The reason for inhibition of fat oxidation at higher intensities is given by the inhibition of mobilization of long-chain fatty acids from subcutaneous adipose tissue, 35 the limited entry of long-chain fatty acids into the mitochondria for oxidation 36 and the inhibition of the oxidation of intramuscular triglycerides.…”
Section: Fitness Levelmentioning
confidence: 99%
“…34 The reason for inhibition of fat oxidation at higher intensities is given by the inhibition of mobilization of long-chain fatty acids from subcutaneous adipose tissue, 35 the limited entry of long-chain fatty acids into the mitochondria for oxidation 36 and the inhibition of the oxidation of intramuscular triglycerides. 33 With increasing intensity, carbohydrate oxidation is increased, whereas fat oxidation is reduced 37 and lactate fails to be completely eliminated. 38 The elimination of lactate in SCI could be reduced compared to ablebodied persons due to differences in muscle mass and muscle fibre distribution.…”
Section: Fitness Levelmentioning
confidence: 99%
“…A relatively rapid regulation is suggested by clinical studies showing that moderate prolonged exercise decreases IMCL within hours (12). However, which factors control the accumulation of IMCL and how rapidly this occurs is largely unknown.…”
mentioning
confidence: 99%